Investigation of the knowledge level, attitudes, and behaviors about sun protection and sunscreen in adolescent athletes - Havva Hilal Ayvaz; Hüseyin Tolga Acar; Sabriye Ercan; Cem Çetin (Galenos Publishing House, 2021)
Background and Design: This study aims to evaluate the knowledge level of adolescent licensed athletes between the ages of 12 and 18 years about sun protection and sunscreen use. Materials and Methods: In our province, 644 adolescents engaged in sports under license were included in the study. Samples were selected by the stratification method. The questionnaires were filled by face-to-face interview techniques in the athletes' training environment. Demographic data of the participants were recorded. Then, the participants were administered the Sun Protection and Use of Sunscreen Change Stages scales and Sun Protection Behavior scale, Sun Protection Decision Balance scale, Sun Protection Self-Efficacy scale, which were prepared based on the transtheoretical model (TTM) theory. Adolescent athletes were divided into two groups according to the place where they train/match as "Indoor" (Groupindoor) and "Outdoor" (Groupoutdoor) athletes. Results: While 59% (n=380) of the athletes participate in training/competition indoors (Groupindoor), 41% (n=264) of the athletes participate in outdoors (Groupoutdoor). According to TTM; 60.2% (n=388) of the athletes are at the stage of "precontemplation", and 12.7% (n=82) of the Sun Protection Change Stages are "maintenance". On the other hand, it was determined that 69.1% (n=445) of the athletes were in the step of "precontemplation", and 10.7% (n=69) of the "maintenance" step of the use of sunscreen change stage scale. The scale results administered to adolescent athletes did not differ between the groups (p˃0.05). Conclusion: In light of the data we obtained from our study, it was determined that the adolescent age group athletes have a low level of knowledge about sun protection, sunscreen use, and skin cancer, regardless of sports discipline in the outdoors or indoors. We recommend training and counseling for all adolescent athletes about the harmful effects of the sun.